AKAL MENURUT CENDEKIAWAN MUSLIM KLASIK DAN KONTEMPORER - Lubis, Sakban (Lembaga Jurnal dan Seminar Universitas Pembangunan Panca Budi, 2018)
The word al-‘aql etimologically has various meanings, they are the persistence of something (al-tatsabbut fi al-umur), restraint and trying to hold back (al-imsāk wa al-imtisāk), or preventing (al-man'u) as in the saying: